FORENSIC EXAMINATION OF WILD FLORA AND FAUNA: A NEW BRANCH OF FORENSIC INQUIRY IN FORENSIC SCIENCE ORGANIZATIONS OF THE RUSSIAN MINISTRY OF JUSTICE - V. Gulevskaya (Теория и практика судебной экспертизы, 2015)
The paper examines key trends in providing forensic support for investigation of crimes against wild plants and animals, and argues for the need to develop wildlife forensics as an independent branch of inquiry pursued by forensic science organizations of the Russian Ministry of Justice.